Integrasi Nilai Kebhinekaan Pada Anak Usia Dini Melalui Projek Penguatan Profil Pelajar Pancasila Di TK Dharma Wanita Wanengpaten: Integration of Diversity Values in Early Childhood Through Project on Strengthening the Profile of Pancasila Students at Dharma Wanita Wanengpaten Kindergarten - Dwita, Dwita Dela Selvia; Al-Fahmi, Sari Nadhifa; Karisma, Dwi Yogi; Lestariningrum, Anik (Universitas Nusantara PGRI Kediri, 2023)
The purpose of writing the results of this study is to describe the integration of diversity values applied to early childhood through project-based activities that aim to strengthen the profile of Pancasila students. The problem faced is that there is still a misconception about understanding project activities rather than teaching children about the values of strengthening Pancasila, more on the results in the form of products that can be shown. Responding to this problem for the writer is very important when the foundational development phase of early childhood is taught about basic values in understanding and respecting differences, cultural diversity as part of the elaboration of Pancasila values in everyday life. The research design chosen was qualitative by collecting data using direct observation techniques, and documenting the results of project learning activities to strengthen the profile of Pancasila students. The data analysis technique used is descriptive qualitative analysis by processing the data in a theoretical and empirical study based on the results of direct observation then concluded and described in a narrative manner. The results of this study found that early childhood activities in process-oriented projects, especially habituation activities, make children recognize the value of diversity without having to explain it in a difficult way, but practice it directly. The recommendations given from the results of this study may be an inspiration for educators, parents, and related parties in developing educational programs that encourage diversity from an early age, so that the next generation of the nation can grow as individuals who respect cultural diversity, build harmonious relationships, and strengthen unity. in a multicultural society.